Influence of Weight Loss Attempts on Bariatric Surgery Outcomes. Issue 10 (October 2016) - Deb, Sayantan; Voller, Lindsey; Palisch, Chase; Ceja, Omar; Turner, Wes; Rivas, Homero; Morton, John M.
Many payors require an additional attempt at nonsurgical weight loss before approval of bariatric procedures. This study evaluates this requirement by characterizing the prior weight loss attempts (WLAs) undergone by bariatric surgery patients and correlating those attempts to postoperative weight loss outcomes. Number and duration of WLAs were obtained from a preoperative clinic assessment. Body mass index (BMI) and percentage of excess weight loss (%EWL) were used to assess weight loss. Kruskal-Wallis and Spearman Correlation tests were performed to analyze data using GraphPad Prism 6. Mean number of WLAs before surgery was 3.5 ± 0.2 attempts, with an average duration of 15.2 ± 1.1 years. There was a significant negative correlation between duration of WLAs and preoperative BMI ( r = -0.2637, P = 0.0025). No significant difference was found for preoperative BMI or mean 12-month %EWL among any WLA groups. The number and duration of dietary attempts before surgery do not significantly affect long-term weight loss outcomes after bariatric surgery. Given these data, an additional preoperative WLA may not be efficacious in improving patients' chances at weight loss.